Numerical Evaluation and Management Suggestions for Heavy Metal Pollution Risks in a Sludge Landfill: A Case Study from Fuyong Landfill, Shenzhen, China - Muyun Sun; Kaiyuan He; Shi Shu (Advances in Civil Engineering)
Despite the extensive attention paid to the transport of heavy metals in sludge landfills, the processes of transporting these pollutants from a landfill to the underground environment are quite complicated and subject to significant uncertainty. In this study, the transport of typical heavy metal pollutants in a sludge landfill through saturated and unsaturated soil zones during rainfall was investigated via numerical modeling. The objectives of the study are to evaluate the heavy metal pollution risk from a sludge landfill under rainfall infiltration conditions and to propose several management suggestions. The results indicate that, during rainfall, heavy metal concentrations at the top of the unsaturated sludge layer decrease rapidly, but they decrease more gradually at the bottom of the layer. The maximum concentration appears in vertical distribution and decreases gradually through the saturated zone. Nickel is the first heavy metal pollutant to break through the low-permeability natural silt barrier. The transport parameters not only influence the simulated time for heavy metal pollutants to break through the silt layer and cause underground environmental pollution but also affect the extent to which the heavy metal pollutants in pore water exceed the guidelines. On the basis of these results, for dredged sludge with heavy metal concentrations significantly exceeding the standard, the concentration of heavy metals in pore water should be reduced before the sludge is landfilled, and a covering layer should be established on the sludge surface to control rainfall infiltration.